To the ends of the earth : and what happened on the way there - Hunter, Malcolm I. (2019)
"An expert on nomadic peoples, Malcolm Hunter shares stories from a lifetime of working in some of the world's most remote, colorful, and neglected communities. In the early 1960s Malcolm and his wife, Jean, arrived in Ethiopia with only their professional skills--medicine and engineering--and a desire to show God's love to those in need. Over the next forty years God would lead them across Africa, through lush hills and scorched bush, to a dozen people groups who hadn't heard the gospel. Wherever the Hunters went, they found that God had been there first." - description of the first edition.
Keywords: Travel -- Personal narratives; Humanitarianism -- Africa -- Personal narratives; Humanitarianism -- Africa -- Religious aspects; Social service -- Africa -- Personal narratives; Social service -- Africa -- Religious aspects; Humanitarianism; Humanitarianism -- Religious aspects; Social service; Social service -- Religious aspects; Travel; Africa; Personal narratives; Travel writing; Travel writing